Slums on Screen World Cinema and the Planet of Slums - Krstić, Igor (Edinburgh University Press, 2016)
From Jacob Riis' How The Other Half Lives (1890) to Danny Boyle's Slumdog Millionaire (2008), Igor Krstić outlines a transnational history of films that either document or fictionalise the favelas, shantytowns, barrios poulares or chawls of our 'planet of slums'.